Toxicity Test Of Burdock (Arctium lappa L) Root Extract On Renal Histopathological Profile And Granulocyte Response In Wistar Rats : Uji Toksisitas Ekstrak Akar Burdock (Arctium lappa L) Terhadap Profil Histopatologi Ginjal Dan Respon Granulosit Tikus Wistar - Dwi Faizatun Nisa; Imam Agus Faizal; Dini Puspodewi (Universitas Muhammadiyah Sidoarjo, 2025)
Burdock (Arctium lappa L) is a medicinal plant widely used in traditional therapy due to its active compounds, including arctigen, and phenolic acids, which possess antioxidant and anti inflammatory pro penties. The study aims to investigate the histopatholohical profile of the kidneys and granulocyte levels in wistar rats after administration of burdock root extract. This study employed an experimental method using 8 male and female wistar rats divided into four groups, an negative control group and treatment groups whith doses 0f 150 mg/kgBB, 300 mg/kgBB, and 450 mg/kgBB. The extract was orally for 28 days. Was performed using Periodic Acid Schiff (PAS) sataining, and granulocyte counts were using a hematology analyzer. The results of kidney tissue examination showed no significant histopatological damage in all treatment groups, some sampeles showed the presence of adipocytes, but without indication of kidey damage. PAS staining showed no glycogen or mucopolysaccharides, which indicate tissue damage. Granulocyte levels in the treatment groups showed varying changes, depending on dose and gender, whit a significant increase in high doses in females. It can be mucopolysaccharides indicating tissue damage. Granulocyte counts in the treatment groups showed varying changes depending on dose and gender, whit a significant increase at high doses in famales. It can be concluded that burdock root extrack dose not cause histopathological kidey tissue damage and is relativeky safe use at low to high doses, but it affects granulocyte counts in a dose and sex dependent manner.